New Equivalent Linear Impact Model for Simulation of Seismic Isolated Structure Pounding against Moat Wall - Yang Liu; Wen-Guang Liu; Xin Wang; Wen-Fu He; Qiao-Rong Yang (Shock and Vibration)
Base-isolated buildings subjected to extreme earthquakes or near-fault pulse-like earthquakes can exceed their design gap distance and impact against the surrounding moat wall. Based on equating energy dissipation and maximum collision compression deformation of isolated structure with the Hertz-damp model and Kevin-Voigt model in the process of collision, an equivalent linear impact model (ELIM) is proposed to better predict impact response of seismic isolated structure. The formula of the equivalent linear stiffness of ELIM is theoretically derived. The effectiveness of ELIM is verified by comparing the results of numerical analyses with the results of pounding experiments. Four near-fault earthquakes are selected to validate rationality and accuracy of the proposed model using numerical analysis. The results indicate that the proposed linear model can nearly capture impact behavior of isolated structure in simulating the pounding-involved structural response.